Gedunin and azadiradione: human pancreatic alpha-amylase inhibiting limonoids from neem (azadirachta indica) as anti-diabetic agents - Ponnusamy, Sudha; Haldar, Saikat; Mulani, Fayaj A.; Smita S. Zinjarde; Thulasiram, Hirekodathakallu; RaviKumar, Ameeta (Plos One, 2015)
Human pancreatic alpha-amylase (HPA) inhibitors offer an effective strategy to lower postprandial hyperglycemia via control of starch breakdown. Limonoids from Azadirachta indica known for their therapeutic potential were screened for pancreatic alpha-amylase inhibition, a known anti-diabetic target. Studies were carried out to reveal their mode of action so as to justify their hypoglycemic potential. Of the nine limonoids isolated/semi-synthesized from A. indica and screened for alpha-amylase inhibition, azadiradione and exhibited potential inhibition with an IC50 value of 74.17 and 68.38 mu M, respectively against HPA under in vitro conditions. Further screening on AR42J alpha-amylase secretory cell line for cytotoxicity and bioactivity revealed that azadiradione and gedunin exhibited cytotoxicity with IC50 of 11.1 and 13.4 mu M. Maximal secreted alpha-amylase inhibition of 41.8% and 53.4% was seen at 3.5 and 3.3 mu M, respectively. Michaelis-Menten kinetics suggested a mixed mode of inhibition with maltopentaose (K-i 42.2, 18.6 mu M) and starch (K-i' 75.8, 37.4 mu M) as substrate with a stiochiometry of 1: 1 for both azadiradione and gedunin, respectively. The molecular docking simulation indicated plausible p-alkyl and alkyl-alkyl interactions between the aromatic amino acids and inhibitors. Fluorescence and CD confirmed the involvement of tryptophan and tyrosine in ligand binding to HPA. Thermodynamic parameters suggested that binding is enthalpically and entropically driven with Delta G degrees of -21.25 kJ mol(-1) and -21.16 kJ mol(-1) for azadiradione and gedunin, respectively. Thus, the limonoids azadiradione and gedunin could bind and inactivate HPA (anti-diabetic target) and may prove to be lead drug candidates to reduce/control post-prandial hyperglycemia.